Triglyceride-glucose index is independently associated with fatty pancreas disease in Chinese elderly - Mi, Weinuo; Zhang, Yuzhi; Wang, Qifeng; Ding, Wenbo; Mao, Xiaodong; Sun, Yu; Li, Xingjia; Liu, Chao; Xu, Shuhang (BMC endocrine disorders, 2025)
Objective To determine the prevalence of fatty pancreas disease (FPD) diagnosed by transabdominal ultrasound in Chinese elderly aged 65 years and above to explore the correlation between triglyceride glucose index (TyG index) and FPD and its severity, and to evaluate the ability of TyG index to identify FPD and its severity. Methods The study population was derived from the Thyroid Diseases in Older Population: Screening, Surveillance, and Intervention (TOPS) study conducted in the iodine-adapted areas of Jiangsu Province from May to July 2021. A total of 567 participants aged 65 years and above in rural areas were included in the final analysis. TyG index was calculated by the established formula: Ln [TG (mg/dL) × FBG (mg/dL)/2]. FPD and the degree of intra-pancreatic fat deposition (IPFD) were diagnosed by abdominal ultrasound. The logistic regression model was performed to determine the correlation between clinical parameters, including TyG index, and FPD and its severity. The diagnostic power of TyG index was assessed by receiver operating characteristic curve (ROC). Results Overall, 72.66% (412/567) of subjects had FPD, of which over half had moderate to severe FPD. The proportions of overweight, obesity, NAFLD, and dyslipidemia were significantly higher in the moderate-to-severe FPD group than in the mild FPD group. Multivariate logistic regression showed that TyG index was independently associated with FPD in the elderly population, but was not significantly associated with the severity of IPFD. As the level of TyG index increased, the metabolic disorders in the population worsened and the prevalence of FPD increased significantly. TyG index had a good diagnostic performance for FPD. The combination of BMI or NAFLD and TyG index improved the diagnostic ability for FPD. Conclusion The prevalence of FPD diagnosed by abdominal ultrasound is high in the elderly aged 65 years and above in rural areas in China. TyG index has good identification of FPD but poor recognition of the severity of IPFD. TyG index, when combined with other clinical parameters, may have more diagnostic advantages.